Racionalidade e verossimilhança segundo Karl Popper - Fernando Ruiz Rosario (2018)
The present work intends to analyze the verisimilitudes theory and its importance for the falsiability project of Karl Popper. At rst, we present the metaphysical, epistemological and methodological aspects present in the authors defense of falsiability. For Popper, human knowledge is constructed deductively by a method of trial and error, in a critical and non-justicationist way. However, given the philosophical commitments he assumes, Popper must ensure that the succession of theories occurs on a rational basis, without which they lack the informative and explanatory capacity. We next deal with the theory of likelihood as a possible solution to the problem of choice scientic theories, a solution that resorting to the calculation of truth content. However, as this solution fails, the present work analyzes the possibilities available to the Popperian project, without denying the commitments previously made, presentation of some solutions that arose in defense of Critical Rationalism.